2017
DOI: 10.1038/srep45711
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of membrane-bound fatty acid desaturase genes in Gossypium hirsutum and their expressions during abiotic stress

Abstract: Membrane-bound fatty acid desaturases (FADs) are of great importance and play multiple roles in plant growth and development. In the present study, 39 full-length FAD genes, based on database searches, were identified in tetraploid upland cotton (Gossypium hirsutum L.) and were phylogenetically clustered into four subfamilies. Genomic localization revealed that 34 genes were mapped on 22 chromosomes, and five genes were positioned on the scaffold sequences. The FAD genes of G. hirsutum in the same subfamily ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 50 publications
3
32
0
1
Order By: Relevance
“…To date, the FAD gene family has been identified and characterized in many plants, including 17 FADs in Arabidopsis [21], 29 in soybean [28], 31 in peanut [29], and 41 in Raymond cotton [30]. FAD genes have also been isolated from land cotton [31], sesame [32], sunflower [33] and other plants.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the FAD gene family has been identified and characterized in many plants, including 17 FADs in Arabidopsis [21], 29 in soybean [28], 31 in peanut [29], and 41 in Raymond cotton [30]. FAD genes have also been isolated from land cotton [31], sesame [32], sunflower [33] and other plants.…”
Section: Discussionmentioning
confidence: 99%
“…In an upland cotton ( Gossypium hirsutum L.) study, 39 full-length FAD genes, based on database searches, were identified in tetraploid and were phylogenetically clustered into four subfamilies. Genomic localization revealed that 34 genes were mapped on 22 chromosomes, and five genes were positioned on the scaffold sequences [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…This diversification is enabled by the presence of multigene families; whereas the Arabidopsis genome carries only one copy of AtFAD2, comparative analysis of other species reveals that many plant genomes carry multiple FAD2 homologs. For example, soybean has seven FAD2 gene family members (Lakhssassi et al, 2017), cotton has nine (Feng et al, 2017), safflower has 11 (Cao et al, 2013), and parsley (Petroselinum crispum) and carrot (Daucus carota ssp. sativus) have 17 and 24, respectively, the highest number of family members documented so far, indicating that functional divergence of FAD2 is not limited to oil seed crops (Somssich et al, 1989;Busta et al, 2018).…”
mentioning
confidence: 99%
“…In addition to encoding catalytic diversity, FAD2 homologs also show diversity in their expression patterns. While some FAD2 genes are targeted to the seeds, others are ubiquitous or specific to other organs; for example, transcript profiling of the FAD2 gene family in cotton and safflower revealed that developing seeds, roots, stems, and leaves expressed overlapping but distinct sets of FAD2 homologs (Cao et al, 2013;Feng et al, 2017). In addition, different members of the FAD2 family in soybean varied in their responsiveness to chilling and salinity (Feng et al, 2017), two abiotic stresses known to upregulate FAD2 expression (Wang et al, 2004;Kargiotidou et al, 2008;Teixeira et al, 2009;Zhang et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation